Botanical Defence: Exploring Plant-Derived Vaccines for Animal Health – An Overview - Khandelwal, Shivali; Rachel, Sharolin; Yadav, Vishal; Kour, S Simran; Bhati, Taruna (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Plant-based vaccines have emerged as a revolutionary approach in the field of immunization, offering numerous advantages over  conventional vaccine production methods. This article explores the concept of plant-derived vaccines and their potential applications  in animal health and sustainable agriculture. Utilizing plants as bioreactors, plant-based vaccines produce specific antigens that trigger  a robust immune response upon ingestion by animals. These vaccines are pathogen-free and do not require refrigeration, making them  cost-effective and accessible, especially in resource-limited regions. Moreover, plant-based vaccines are safer than traditional vaccines,  as they contain no live pathogens, and they have demonstrated high stability and scalability in antigen production. Maintaining dosage  consistency and adhering to Good Manufacturing Practice (GMP) standards are essential for ensuring vaccine quality and efficacy.  Plant-based vaccines represent a paradigm shift in vaccine production and offer a pathway to a healthier and more resilient future.  With further advancements and collaboration among stakeholders, plant-based vaccines have the potential to impact global health,  addressing disease challenges in animals and humans alike.
Keywords: Antigens; , Bioreactors; Cost-effective; Goats; Plant-based vaccines